ANEKA GARAP LADRANG PANGKUR - Sugimin Sugimin (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2013)
Along with the developments in karawitan treatment, Ladrang Pangkur Paripurna has experienced quite significant developments in its musical treatment. Beginning as a gending langendriyan, it subsequently developed into a variety of interpretations of Pangkur, performed for a variety of purposes. The musical interpretation of performances of Ladrang Pangkur Paripurna in the form of different interpretations of instrumentation, rhythms, dynamics, tuning (laras), mode (pathet), vocal style, and so on, have been manifested in a variety of interpretations of Pangkur, named according to their dominant elements of treatment, such as Pangkur Pamijèn, Pangkur Jênglèng, Pangkur Gobyog, Pangkur Céngkok Kethoprak, and Pangkur Wolak-walik. A number of interpretations of Pangkur by Ki Nartasabda, such as Pangkur Gala-Gala, Pangkur Padhang Rêmbulan, Pangkur Cêluk, and Pangkur Rog-rog Asêm, are based on vocal interpretations. Due to the appearance of various interpretations or treatments of Pangkur, Ladrang Pangkur has become increasingly popular among the karawitan community. Key words: Ladrang Pangkur, development, musical treatment